Media dan Konstruksi Identitas Kepemimpinan - Nanang Mizwar Hasyim (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2018)
This research is motivated by the authors' interest in repeated and ongoing news with certain strategies in the context of the relationship between the fight for public opinion, conducted by Detik.com and Kompas.Com related to Ahok's leadership identity as a phenomenal Jakarta Governor and is also a candidate in the DKI Jakarta Gubernatorial Election 2017. Population taken is news for four years during Ahok served as Governor to replace Joko Widodo until the implementation of Jakarta Gubernatorial election 2017. While the sample is news that tell about Ahok’s leadership. This research uses social semiotics method of M.A.K. Halliday with the aim to describe how the construction of Ahok leadership identity in the news Online media. This study concludes that the news construction conducted by Detik.com on Ahok's leadership identity emphasizes the negative side, where the negative side of Ahok's leadership is emphasized on the arrogant and unethical character. While on Kompas.com's report, Ahok's leadership identity is constructed as a professional, credible, creative and innovative leader in performing his duties as the Governor of DKI Jakarta with emphasis on the competence and credibility. On the consistency side of the media in preaching a reality, the researcher found there is inconsistency in news of Detik.com than Kompas.com, where in the decade ahead of DKI Jakarta Gubernatorial Election 2017, Ahok's leadership identity construction become changed from a negative leadership identity become a positive identity of leadership.